The ethnopolitics of Russia in the Arctic zone: integration, regional multiculturality, and tradition - Maksim Yu. Zadorin; Oleg V. Minchuk (Arctic and North, 2017)
The article is dedicated to the strategic issues of the ethnic policies’ development in the Arctic zone of the Russian Federation. Nowadays the academic knowledge of constitutional law and political science doesn’t demonstrate clear understanding of the Russian ethnic national policy model in the Arctic, there are no comprehensible definitions and criteria, which could be used to estimate the present and desired model satisfying interests of the state and polytechnic society. It is also important to note that the course of certain ethnic processes in Russia and in the Russian Arctic is determined by the state mechanism. Its main instrument is the regulation of public relations with legal and political methods. In this article, the authors tried to understand the political and legal mechanism of the current Russian ethnic policy model in the Arctic. The practical goal is to develop proposals for improving its main components to form a more advanced policy model. The authors identified ten basic elements of the ethnopolitics of Russia in the Arctic zone, embodied in political and legal institutions (including the author’s theoretical ideas about conceptual and categorical apparatus), and indicated eight practical proposals for improving this model.